Measurement of cochlear implant outcomes in goldenhar syndrome: A case report (Indian Journal of Case Reports, 2019)
Goldenhar Syndrome is a rare syndrome which affects most of the characteristic features of that particular individual ranging from inner ear anomalies to renal anomalies. As some individuals have inner ear anomalies, it is important to document the habilitation done for hearing loss. Our article focusses on documenting the outcome of Cochlear Implant over a period of one year in an individual with Goldenhar Syndrome. The paper documents a case of a Goldenhar Syndrome child of two years of age who has undergone Cochlear implantation and outcomes of implantation was measured over a period of one year. Auditory habilitation, behavioural MAPing and parent training were given at regular intervals. Conditioned play audiometry was done at regular intervals to monitor the progress of the child. At the end of one year, speech and language skills and auditory verbal skills were assessed. It was found out that, there was an improvement in all parameters but at a lesser rate, hence concluding there should be adequate stimulation to yield better results.